One pot synthesis of Cu2O/RGO composite using mango bark extract and exploration of its electrochemical properties - Kumar, J. Sharath; Jana, Milan; Khanra, Partha; Samanta, Pranab; Koo, Hyeyoung; Murmu, Naresh Chandra; Kuila, Tapas (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
A facile and eco-friendly approach for the simultaneous reduction of graphene oxide (GO) as well as copper acetate to prepare Cu2O decorated reduced GO (RGO) has been demonstrated. Herein, an easily available and naturally occurring mango bark (M. indica) extract has been used as the reducing agent instead of hazardous and toxic chemicals. Fourier transform infrared and X-ray photoelectron spectroscopy have been performed to confirm the removal of oxygen functional groups from the surface of GO. X-ray diffraction pattern reveals the formation of Cu2O nanoparticles (NPs). Morphological characterization was carried out using field emission scanning electron and transmission electron microscopy to confirm the decoration of RGO with Cu2O NPs. The electrocatalytic behaviour of the RGO/Cu2O composite has been carried by cyclic voltammetry and amperometric analysis. It shows the utility of the RGO/Cu2O composite as an electrochemical sensor towards H2O2 detection. The sensitivity and limit of detection for the composite are found to be 7.435 mu A mu M-1 & 42.35 nM, respectively. The RGO/ Cu2O//RGO asymmetric supercapacitor device shows the specific capacitance (SC) of 195 F g(-1) at a current density of 2 A g(-1) and energy density of 37.7 Wh kg(-1) with 79% retention in SC after 5000 charge-discharge cycles. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: HYDROGEN-PEROXIDE; GRAPHENE OXIDE; FACILE SYNTHESIS; CHEMICAL-REDUCTION; PERFORMANCE; NANOPARTICLES; GAS; NANOSTRUCTURES; NANOCOMPOSITE; ELECTRODES